Application of Fe / Si bimetal pillared montmorillonite composite material in in-situ remediation of polluted sediments
By preparing Fe/Si bimetallic pillared montmorillonite composite materials, the problem of easy aggregation of iron oxides in lake sediments was solved, the generation of reactive oxygen species was significantly increased, and the efficient degradation and remediation of pollutants were achieved.
Patent Information
- Application Number
- CN202411442616.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-07
AI Technical Summary
In existing technologies, iron oxides and iron sulfides tend to aggregate in lake sediments, resulting in low efficiency of electron transfer and energy transition, making it difficult to effectively increase the yield of reactive oxygen species and affecting the remediation effect of pollutants.
A Fe/Si bimetallic pillared montmorillonite composite material was used. The preparation process involved mixing FeCl3·6H2O and NaSiO3 solutions with montmorillonite and calcining it at high temperature to form a stable bimetallic pillared structure, thereby increasing the generation of reactive oxygen species in the sediment.
It significantly increased the generation of reactive oxygen species in sediments and improved the degradation efficiency of pollutants, especially polycyclic aromatic hydrocarbons, antibiotics and estrogens, thus achieving efficient in-situ remediation of polluted sediments.
Smart Images

Figure CN119259048A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of efficient restoration of lake sediments, and specifically relates to the application of a Fe / Si bimetallic pillared montmorillonite composite material in in-situ restoration of contaminated sediments. Background Art
[0002] Lake reactive oxygen species are highly active substances generated by oxygen in lake water or sediment during electron transfer. Typical lake reactive oxygen species include hydroxyl radicals (·OH), singlet oxygen ( 1 O2), excited triplet oxygen ( 3 CDOM * ) etc. Active species have high redox sites and can indiscriminately oxidize carbon, nitrogen, phosphorus and organic pollutants in water and sediments. They play an important role in the circulation of lake biogenic elements and the migration and transformation of pollutants, and can significantly affect the water quality and ecosystem structure of lakes.
[0003] Improving the efficiency of electron transfer and energy transition of reducing substances such as iron in sediments is an effective method to increase the production of reactive oxygen species. It is generally believed that the production of reactive oxygen species can be increased by adding iron oxides and iron sulfides to surface sediments. However, iron oxides and iron sulfides tend to agglomerate in sediments, reducing the efficiency of electron transfer and energy transition, so the increase in the production of reactive oxygen species in sediments is limited. Montmorillonite is a layered mineral composed of extremely fine particles of hydrous aluminum silicate, which is widely distributed in lake sediments. Montmorillonite has good dispersibility. After hydration, its interlayer exchangeable cations can be exchanged with other surrounding metal cations, which will increase the interlayer spacing of montmorillonite. After high-temperature calcination, a stable structure with high activity can be formed. The metal ions iron and silicon have variable valence states and can be stably pillared in the interlayer of montmorillonite by ion exchange to form highly active bimetallic pillared montmorillonite. However, there are few reports on the methods and applications of bimetallic pillared montmorillonite to increase the production of reactive oxygen species in lake sediments.
[0004] Therefore, developing a method to increase the production of reactive oxygen species in sediments during water level fluctuations and then applying it to the remediation of contaminated sediments can maximize the ecological, environmental, economic and social benefits, which is of great strategic significance for the remediation of pollution in lake sediments, riparian sediments, coastal sediments, soil, etc. Summary of the invention
[0005] In order to solve the above-mentioned defects and shortcomings in the prior art, the present invention provides an application of an Fe / Si bimetallic pillared montmorillonite composite material in in-situ remediation of contaminated sediments. The Fe / Si bimetallic pillared montmorillonite composite material can significantly increase the production of active oxygen species in sediments during lake water level fluctuations, thereby achieving the purpose of in-situ remediation of sediments.
[0006] In order to solve the above technical problems, the present invention provides an application of a Fe / Si bimetallic pillared montmorillonite composite material in in-situ remediation of contaminated sediments, wherein the Fe / Si bimetallic pillared montmorillonite composite material is mixed with sediments in a water level fluctuation process to degrade antibiotics, estrogen or organic pesticide residues in the sediments;
[0007] The preparation method of the Fe / Si bimetallic pillared montmorillonite composite material comprises the following steps:
[0008] S1 Montmorillonite pretreatment: Add montmorillonite to deionized water and stir in a water bath to fully swell the montmorillonite;
[0009] S2 bimetallic loading: FeCl3·6H2O solution and NaSiO3 solution are slowly added dropwise to the montmorillonite suspension, stirred and aged overnight, and then centrifuged, dried and ground to obtain Fe / Si bimetallic loaded montmorillonite; wherein the concentration of FeCl3·6H2O solution is 0.35-0.55M, and the concentration of NaSiO3 solution is 0.60-0.90M;
[0010] S3 bimetallic pillared montmorillonite: The Fe / Si bimetallic loaded montmorillonite is placed in a muffle furnace and calcined at 300-500°C for 2-4 hours. After cooling, the Fe / Si bimetallic pillared montmorillonite is obtained.
[0011] Furthermore, the mass ratio of deionized water to montmorillonite is 35:1-45:1, and the water bath temperature is 30-35°C.
[0012] Further, in step S2, the concentration of FeCl3·6H2O is 0.45-0.50M, and the concentration of NaSiO3 solution is 0.70-0.80M.
[0013] Further, in step S2, the volume ratio of FeCl3·6H2O concentration to montmorillonite suspension is 0.95:1 to 1.05:1, and the volume ratio of NaSiO3 solution to montmorillonite suspension is 0.95:1 to 1.05:1.
[0014] Furthermore, in step S3, the calcination temperature is 350-450° C., and the calcination time is 2.0-2.5 h.
[0015] Furthermore, the mass ratio of the bimetallic pillared montmorillonite composite material to the sediment is 1:1000 to 1:100.
[0016] Beneficial technical effects achieved by the present invention:
[0017] 1. The synthesis method of bimetallic pillared montmorillonite is simple, easy and low-cost.
[0018] 2. The synthesized bimetallic pillared montmorillonite is non-toxic, harmless and stable. It is not easy to agglomerate and compact when added to sediments, and has no toxic effect on the lake water and sediment microbial ecosystem.
[0019] 3. The addition of bimetallic pillared montmorillonite can significantly increase the amount of active oxygen species produced in sediments during water level fluctuations. 3 DOM * The generation volume increased by 4.87 times, 1 The generation of O2 increased by 5.04 times, and the generation of ·OH increased by 5.13 times, which can effectively repair the sediments.
[0020] 4. The addition of bimetallic pillared montmorillonite can significantly improve the degradation efficiency of sediment pollutants, among which the degradation efficiency of polycyclic aromatic hydrocarbons is increased by 1.58 times, the degradation efficiency of antibiotics is increased by 2 times, and the degradation efficiency of estrogen is increased by 1.79 times. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a SEM image of the Fe / Si bimetallic pillared montmorillonite composite material prepared in Example 2 of the present invention;
[0022] Figure 2 This is a schematic diagram of a lake water level fluctuation simulation column of the present invention;
[0023] Figure 3 It is a curve diagram showing the effect of the Fe / Si bimetallic pillared montmorillonite composite material of the present invention on the production of excited triplet oxygen in sediments;
[0024] Figure 4 It is a curve diagram showing the effect of the Fe / Si bimetallic pillared montmorillonite composite material of the present invention on the production of excited singlet oxygen in sediments;
[0025] Figure 5 It is a curve diagram showing the effect of the Fe / Si bimetallic pillared montmorillonite composite material of the present invention on the yield of hydroxyl radicals excited by sediments;
[0026] Figure 6 The degradation efficiency curve of the Fe / Si bimetallic pillared montmorillonite composite material of the present invention on polycyclic aromatic hydrocarbons in sediments;
[0027] Figure 7This is a curve diagram of the degradation efficiency of the Fe / Si bimetallic pillared montmorillonite composite material of the present invention on antibiotics in sediments;
[0028] Figure 8 This is a curve diagram of the degradation efficiency of the Fe / Si bimetallic pillared montmorillonite composite material of the present invention on estrogen in sediments. DETAILED DESCRIPTION
[0029] The present invention will be further described below in conjunction with specific examples. The following examples are only used to more clearly illustrate the technical solutions of the present invention, and are not intended to limit the scope of protection of the present invention.
[0030] The present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0031] Reagents required for the following examples: FeCl3·6H2O and NaSiO3 were purchased from Sinopharm Group, and montmorillonite was purchased from Sinopharm.
[0032] The present invention provides an application of an Fe / Si bimetallic pillared montmorillonite composite material in in-situ remediation of contaminated sediments. The Fe / Si bimetallic pillared montmorillonite composite material is mixed with sediments in a water level fluctuation process to degrade antibiotics, estrogen, organic pesticide residues or chemical fertilizer residues in the sediments; wherein the mass ratio of the Fe / Si bimetallic pillared montmorillonite composite material to the sediment (wet weight) is 1:1000-1:100. As an embodiment, the mass ratio of the Fe / Si bimetallic pillared montmorillonite composite material to the sediment is 1:600-1:200. As a more preferred embodiment, it can be 1:500.
[0033] The preparation method of the Fe / Si bimetallic pillared montmorillonite composite material comprises the following steps:
[0034] S1 Montmorillonite pretreatment: Add montmorillonite to deionized water and stir in a water bath to fully swell the montmorillonite;
[0035] S2 bimetallic loading: FeCl3·6H2O solution and NaSiO3 solution were slowly added dropwise to the montmorillonite suspension, stirred for 7 h and aged overnight, then centrifuged, dried and ground to obtain Fe / Si bimetallic loaded montmorillonite;
[0036] S3 bimetallic pillared montmorillonite: The Fe / Si bimetallic loaded montmorillonite is placed in a muffle furnace and calcined at 300-500°C for 2-4 hours. After cooling, the Fe / Si bimetallic pillared montmorillonite is obtained.
[0037] Example 1
[0038] Preparation method of Fe / Si bimetallic pillared montmorillonite composite material:
[0039] S1 montmorillonite pretreatment: montmorillonite was added to deionized water and stirred in a water bath to fully swell the montmorillonite; wherein the mass ratio of deionized water to montmorillonite was 35:1 and the water bath temperature was 30°C;
[0040] S2 bimetallic loading: FeCl3·6H2O solution and NaSiO3 solution were slowly added dropwise to the montmorillonite suspension, stirred for 7 hours and aged overnight, then centrifuged, dried and ground to obtain Fe / Si bimetallic loaded montmorillonite; the concentration of FeCl3·6H2O solution was 0.35M, and the concentration of NaSiO3 solution was 0.70M; and the volume ratio of FeCl3·6H2O solution and NaSiO3 solution to montmorillonite suspension was 0.95:1;
[0041] S3 bimetallic pillared montmorillonite: The Fe / Si bimetallic loaded montmorillonite was placed in a muffle furnace and calcined at 300°C for 2h. After cooling, the Fe / Si bimetallic pillared montmorillonite was obtained.
[0042] Example 2
[0043] Preparation method of Fe / Si bimetallic pillared montmorillonite composite material:
[0044] S1 montmorillonite pretreatment: montmorillonite was added to deionized water and stirred in a water bath to fully swell the montmorillonite; wherein the mass ratio of deionized water to montmorillonite was 40:1 and the water bath temperature was 32°C;
[0045] S2 bimetallic loading: FeCl3·6H2O solution and NaSiO3 solution were slowly added dropwise to the montmorillonite suspension, stirred for 7 hours and aged overnight, then centrifuged, dried and ground to obtain Fe / Si bimetallic loaded montmorillonite; the concentration of FeCl3·6H2O solution was 0.45M, and the concentration of NaSiO3 solution was 0.60M; and the volume ratio of FeCl3·6H2O solution and NaSiO3 solution to montmorillonite suspension was 1:1;
[0046] S3 bimetallic pillared montmorillonite: The Fe / Si bimetallic loaded montmorillonite was placed in a muffle furnace and calcined at 400°C for 3h. After cooling, the Fe / Si bimetallic pillared montmorillonite was obtained.
[0047] Example 3
[0048] Preparation method of Fe / Si bimetallic pillared montmorillonite composite material:
[0049] S1 montmorillonite pretreatment: montmorillonite was added to deionized water and stirred in a water bath to fully swell the montmorillonite; wherein the mass ratio of deionized water to montmorillonite was 45:1 and the water bath temperature was 35°C;
[0050] S2 bimetallic loading: FeCl3·6H2O solution and NaSiO3 solution were slowly added dropwise to the montmorillonite suspension, stirred for 7 hours and aged overnight, then centrifuged, dried and ground to obtain Fe / Si bimetallic loaded montmorillonite; the concentration of FeCl3·6H2O solution was 0.55M, and the concentration of NaSiO3 solution was 0.80M; and the volume ratio of FeCl3·6H2O solution and NaSiO3 solution to montmorillonite suspension was 1.05:1;
[0051] S3 bimetallic pillared montmorillonite: The Fe / Si bimetallic loaded montmorillonite was placed in a muffle furnace and calcined at 500°C for 4 hours. After cooling, the Fe / Si bimetallic pillared montmorillonite was obtained.
[0052] Example 4
[0053] Preparation method of Fe / Si bimetallic pillared montmorillonite composite material:
[0054] S1 montmorillonite pretreatment: montmorillonite was added to deionized water and stirred in a water bath to fully swell the montmorillonite; wherein the mass ratio of deionized water to montmorillonite was 40:1 and the water bath temperature was 32°C;
[0055] S2 bimetallic loading: FeCl3·6H2O solution and NaSiO3 solution were slowly added dropwise to the montmorillonite suspension, stirred for 7 hours and aged overnight, then centrifuged, dried and ground to obtain Fe / Si bimetallic loaded montmorillonite; the concentration of FeCl3·6H2O solution was 0.45M, and the concentration of NaSiO3 solution was 0.60M; and the volume ratio of FeCl3·6H2O solution and NaSiO3 solution to montmorillonite suspension was 1.05:1;
[0056] S3 bimetallic pillared montmorillonite: The Fe / Si bimetallic loaded montmorillonite was placed in a muffle furnace and calcined at 400°C for 3h. After cooling, the Fe / Si bimetallic pillared montmorillonite was obtained.
[0057] Example 5
[0058] Preparation method of Fe / Si bimetallic pillared montmorillonite composite material:
[0059] S1 montmorillonite pretreatment: montmorillonite was added to deionized water and stirred in a water bath to fully swell the montmorillonite; wherein the mass ratio of deionized water to montmorillonite was 45:1 and the water bath temperature was 32°C;
[0060] S2 bimetallic loading: FeCl3·6H2O solution and NaSiO3 solution were slowly added dropwise to the montmorillonite suspension, stirred for 7 hours and aged overnight, then centrifuged, dried and ground to obtain Fe / Si bimetallic loaded montmorillonite; the concentration of FeCl3·6H2O solution was 0.45M, and the concentration of NaSiO3 solution was 0.60M; and the volume ratio of FeCl3·6H2O solution and NaSiO3 solution to montmorillonite suspension was 0.95:1;
[0061] S3 bimetallic pillared montmorillonite: The Fe / Si bimetallic loaded montmorillonite was placed in a muffle furnace and calcined at 400°C for 3h. After cooling, the Fe / Si bimetallic pillared montmorillonite was obtained.
[0062] Taking Example 2 as an example, the Fe / Si bimetallic pillared montmorillonite composite material was characterized and tested, and its scanning electron microscope (SEM) image is as follows: Figure 1 As shown, A is a SEM image of montmorillonite, and B is a SEM image of a Fe / Si bimetallic pillared montmorillonite composite material. It can be clearly seen from the figure that the structure of the Fe / Si bimetallic pillared montmorillonite composite material has changed greatly compared to montmorillonite, and the interlayer spacing has increased. This may be because after montmorillonite is hydrated, its interlayer exchangeable cations are exchanged with the surrounding Fe and Si cations, thereby expanding its interlayer spacing, and then after high-temperature calcination, a stable bimetallic pillared montmorillonite structure with high activity is formed.
[0063] Experimental Example 1 Effect of Fe / Si bimetallic pillared montmorillonite composites on the production of active oxygen species in sediments
[0064] 1. Make a simulation column for lake water level fluctuation process: add sediments from the West Lake area of Poyang Lake into a polytetrafluoroethylene cylinder, the sediment height is >40cm, the height / diameter of the cylinder is 5:1-10:1, set up water inlets and outlets in the overlying part, and set up a drain at the bottom of the cylinder; simulate the four cycles of the lake's flooding period, flood period, receding period and dry period according to the water level rise and fall in different periods, each cycle is 7 days. Figure 2 shown.
[0065] 2. In a lightless or weak light environment with a light intensity of <50 lux, the Fe / Si bimetallic pillared montmorillonite composite materials prepared in Examples 1-5 were respectively put into simulated columns of the flood period, the abundant flood period, the receding flood period and the dry season, with each cycle lasting 7 days; the mass ratio of the Fe / Si bimetallic pillared montmorillonite composite materials to the sediment in the simulated columns was 1:500.
[0066] 3. Detection of reactive oxygen species: After the treatment, 0.8-1.2 g of sediment samples were collected from the simulated columns of the flood period, flood period, receding period, and dry period, respectively, and added to 5 mL stoppered centrifuge tubes, and then 2,4,6-trimethylphenol (TMP, 3DOM* probe, CAS No. 527-60-6, purchased from Sinopharm Group), furfuryl alcohol (FFA, 1O2 probe, CAS No. 98-00-0, purchased from Sinopharm Group) and benzene (·OH probe, CAS No. 71-43-2, purchased from Sinopharm Group) were added respectively. The final concentrations of the three fluorescent probes were all 0.8-1.3 mM;
[0067] The concentrations of FFA, TMP and phenol were determined by high performance liquid chromatography. A C18 chromatographic column (150 mm × 4.6 mm × 5 μm) was selected and equipped with a UV detector. Organic alcohol and inorganic acid were selected as eluents for FFA, TMP and phenol, and an automatic injection method was used. The sample injection volume was 15 to 30 μL, preferably 20 to 25 μL; the injection flow rate was 0.3 to 0.6 mL / min, preferably 0.4 to 0.5 mL / min. The retention time of TMP was 10.5 to 11.5 min, and the detection wavelength was 217 to 222 nm; the retention time of FFA was 4.0 to 4.4 min, and the detection wavelength was 228 to 233 nm; the retention time of phenol was 3.5 to 4.0 min, and the detection wavelength was 208 to 215 nm.
[0068] As an example, the calculation formulas for the generation rates and steady-state concentrations of the three reactive oxygen species are as follows:
[0069] 1) Hydroxyl radical ·OH generation rate (R ·OH ) is calculated as shown in formula (1):
[0070]
[0071] In the formula, R Phenol is the rate of phenol formation from benzene during water level fluctuation, R0 is the rate of phenol formation in ultrapure water; Σ i k Si [S i ]=5×105M-1s-1, which is the first-order kinetic constant of the quenching reaction between OH and other substances; k Benzene,·OH =7.8×109M-1s-1, which is the secondary reaction rate constant of benzene reacting with ·OH to generate phenol; [Benzene]0 is the initial concentration of benzene. Under water level fluctuation conditions, ∑ i k Si [S i ] is usually less than 5×105s-1, ∑ i k Si [S i] can be ignored. Therefore, formula (1) can be simplified to formula (2):
[0072] R ·OH =(0.95) -1 (R Phenol -R0) (2)
[0073] When the concentration of benzene as the capture agent is low, the steady-state concentration of OH can be obtained, that is,
[0074]
[0075] 2) Singlet oxygen 1 O2 generation rate The calculation of is shown in formula (3):
[0076]
[0077] In the formula, R FFA is the experimentally determined initial reaction rate of FFA, R0 is the reaction rate of FFA under the condition of no water level fluctuation; is the rate constant of the reaction between FFA and 1O2; [FFA]0 is the initial concentration of probe FFA; is the quenching rate constant of 1O2 colliding with water molecules. When the concentration of the capture agent FFA is extremely low, the steady-state concentration of 1O2 can be obtained, that is,
[0078] 3) Triplet oxygen 3DOM* generation rate The calculation of is shown in formula (4):
[0079]
[0080] In the formula, R TMP is the experimentally determined initial reaction rate of TMP, R0 is the reaction rate of TMP under the condition of no water level fluctuation; About 3×109M-1s-1, which is the secondary rate constant of the reaction between TMP and 3DOM*; k′ is about 5×105s-1, which is the primary kinetic constant of other quenching processes. No TMP conversion was detected under the condition of no water level fluctuation, so the influence of microbial reaction on the research results can be ruled out, so R TMP -R0 can represent the consumption rate of TMP. When the concentration of the capture agent TMP is extremely low, a steady-state concentration of 3DOM* can be obtained, that is,
[0081] Test results such as Figure 3-Figure 5 As shown. Figure 3-Figure 5 It can be seen that in the dry season, after the simulated column is treated with Examples 1-5, 3 DOM *, 1 The maximum concentrations of O2 and OH were significantly increased, especially in Example 2. 3 DOM * , 1 The maximum concentrations of O2 and ·OH were 1086 μmol / kg, 1347 μmol / kg, and 12.37 μmol / kg, respectively, which were 4.87 times, 5.04 times, and 5.13 times that of the control group.
[0082] The composite material prepared in Example 2 was selected to treat simulated sediment columns from different sources. The test results are shown in Table 1.
[0083] Table 1
[0084]
[0085] As can be seen from Table 1, the Fe / Si bimetallic pillared montmorillonite composite material prepared in Example 2 can significantly increase the yield of three active oxygen species when treating sediments from different waters, which also provides a solid theoretical basis for in situ remediation of sediments.
[0086] Test Example 2
[0087] Degradation of pollutants in sediments by Fe / Si bimetallic pillared montmorillonite composite materials: The Fe / Si bimetallic pillared montmorillonite composite materials prepared in Example 2 were selected to treat the sediments to be tested, and the degradation efficiency of different pollutants in different samples to be tested was detected.
[0088] 1. Detection of degradation of polycyclic aromatic hydrocarbons in organic pesticide residues: Sediment samples from Poyang Lake were collected, and some gravel, roots and plant residues visible to the naked eye were removed and divided into two parts: one was a control group without any additions, and the other was added with the Fe / Si bimetallic pillared montmorillonite composite material prepared in Example 2, and the mass ratio of the composite material to the sediment was 1:300. Subsequently, the control group and the bimetallic pillared montmorillonite group sediments were respectively loaded into a lake water level fluctuation simulation column. During the simulation process, each cycle of the flood season, the high water season, the receding water season and the dry season lasted for 8 days. Surface sediment samples were collected every other day, and TMP, FFA and benzene capture agents were added respectively. High performance liquid chromatography was used, and the retention time of TMP was 11.5min, and the detection wavelength was 220nm; the retention time of FFA was 4.1min, and the detection wavelength was 230nm; the retention time of phenol was 3.8min, and the detection wavelength was 210nm. The results are as follows Figure 6 As shown: after the flood period, wet period, receding period and dry period, the degradation efficiency of polycyclic aromatic hydrocarbons in the sediment by the Fe / Si bimetallic pillared montmorillonite composite material group was 1.58 times that of the control group. Therefore, the addition of Fe / Si bimetallic pillared montmorillonite composite material can significantly improve the degradation efficiency of sediment pollutants.
[0089] 2. Antibiotic degradation detection: Collect a sediment sample, remove some visible gravel, roots and plant residues, and add antibiotic pollutants so that the concentration of antibiotic pollutants in the sediment is about 0.5 mg / g. Subsequently, the sediment is divided into two parts: one is a control group without any additions, and the other is added with the Fe / Si bimetallic pillared montmorillonite composite material prepared in Example 2, and the mass ratio of the Fe / Si bimetallic pillared montmorillonite composite material to the sediment is 1:500. Subsequently, the control group and the Fe / Si bimetallic pillared montmorillonite composite material group sediments are respectively loaded into the lake water level fluctuation simulation column. During the simulation process, each cycle of the flood period, flood period, retreat period and dry period lasts for 7 days.
[0090] Surface sediment samples were collected every other day, and TMP, FFA and benzene capture agents were added respectively. High performance liquid chromatography was used, with a TMP retention time of 11.0 min and a detection wavelength of 220 nm; a FFA retention time of 4.2 min and a detection wavelength of 232 nm; and a phenol retention time of 3.7 min and a detection wavelength of 210 nm. Figure 7 As shown: after the flood period, wet period, receding period and dry period, the degradation efficiency of antibiotics in sediments by the Fe / Si bimetallic pillared montmorillonite composite material group was twice that of the control group. Therefore, the addition of Fe / Si bimetallic pillared montmorillonite composite material can significantly improve the degradation efficiency of antibiotics in sediments.
[0091] 3. Estrogen degradation detection: Collect a sediment sample, remove some visible gravel, roots and plant residues, and add estrogen pollutants so that the concentration of estrogen pollutants in the sediment is about 0.05 mg / g. Subsequently, the sediment is divided into two parts: one is a control group without any additions, and the other is added with the Fe / Si bimetallic pillared montmorillonite composite material prepared in Example 2, and the mass ratio of the Fe / Si bimetallic pillared montmorillonite composite material to the sediment is 1:500. Subsequently, the control group and the Fe / Si bimetallic pillared montmorillonite composite material group sediments are respectively loaded into the lake water level fluctuation simulation column. During the simulation process, each cycle of the flood period, flood period, retreat period, and dry period lasts for 7 days.
[0092] Surface sediment samples were collected every other day, and TMP, FFA and benzene capture agents were added respectively. High performance liquid chromatography was used, with a TMP retention time of 11.0 min and a detection wavelength of 220 nm; a FFA retention time of 4.2 min and a detection wavelength of 232 nm; and a phenol retention time of 3.7 min and a detection wavelength of 210 nm. Figure 8As shown: after the flood period, wet period, receding period and dry period, the degradation efficiency of antibiotics in the sediment by the Fe / Si bimetallic pillared montmorillonite composite material group was 1.79 times that of the control group. Therefore, the addition of Fe / Si bimetallic pillared montmorillonite composite material can significantly improve the degradation efficiency of estrogen in the sediment.
[0093] The present invention has been disclosed above with preferred embodiments, but they are not intended to limit the present invention. Any technical solutions obtained by adopting equivalent replacement or equivalent transformation solutions fall within the protection scope of the present invention.
Claims
1. Application of Fe / Si bimetallic pillared montmorillonite composite material in in-situ remediation of contaminated sediments, characterized by: The Fe / Si bimetallic pillared montmorillonite composites were mixed with sediments during water level fluctuations to degrade antibiotics, estrogen or organic pesticide residues in the sediments. The preparation method of the Fe / Si bimetallic pillared montmorillonite composite material comprises the following steps: S1 Montmorillonite pretreatment: Add montmorillonite to deionized water and stir in a water bath to fully swell the montmorillonite; S2 bimetallic loading: FeCl3·6H2O solution and NaSiO3 solution were slowly added dropwise to the montmorillonite suspension, stirred and aged overnight, and then centrifuged, dried and ground to obtain Fe / Si bimetallic loaded montmorillonite; wherein the concentration of FeCl3·6H2O solution was 0.35~0.55M, and the concentration of NaSiO3 solution was 0.60~0.90M; S3 bimetallic pillared montmorillonite: The Fe / Si bimetallic loaded montmorillonite was placed in a muffle furnace and calcined at 300-500°C for 2-4 h. After cooling, the Fe / Si bimetallic pillared montmorillonite was obtained.
2. The use according to claim 1, characterized in that: In step S1, the mass ratio of deionized water to montmorillonite is 35:1-45:1, and the water bath temperature is 30-35°C.
3. The use according to claim 1, characterized in that: In step S2, the concentration of FeCl3·6H2O is 0.45~0.50M, and the concentration of NaSiO3 solution is 0.70~0.80M.
4. The use according to claim 1, characterized in that: In step S2, the volume ratio of FeCl3·6H2O concentration to montmorillonite suspension is 0.95:1-1.05:1, and the volume ratio of NaSiO3 solution to montmorillonite suspension is 0.95:1-1.05:
1.
5. The use according to claim 1, characterized in that: In step S3, the calcination temperature is 350-450° C., and the calcination time is 2.0-2.5 h.
6. The use according to claim 1, characterized in that: The mass ratio of the bimetallic pillared montmorillonite composite material to the sediment is 1:1000~1:100.